PENGARUH PUPUK DAUN GROWMORE DAN HYPONEX TERHADAP PERTUMBUHAN PLANLET DENDROBIUM DIAN AGRIHORTI SECARA IN VITRO - Chitra Priatna (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2019)
ABSTRACTOrchid plants are one of the ornamental plant commodities that have no foodreserves in their seeds and have very fine and small seed sizes making it difficult to propagate naturally. One alternative for the propagation of this plant is to carry out vegetative propagation in vitro or tissue culture. The success of plant tissue culture can not be separated from the role of media composition used. Leaf fertilizer is one of the alternative media that can be used as media material in orchid plant tissue culture because leaf fertilizers contain macro and micro nutrients that can provide nutrient intake to explants to support the growth and development of these explants. Propagation of Dian Agrihorti Dendrobium orchid plant in vitro through callus proliferation using different brands of leaf fertilizer media namely leaf fertilizer hyponex brand and growmore brand. The results of the observation showed that the most proliferative Embryogenic Callus and Proliferation Rate were produced from the treatment of adding 4 ppm growmore, namely 88.42% and 322.41%. For the best color callus parameters generated from the control treatment.